Prognostic significance of systemic immune inflammation index in patients with urothelial carcinoma: a systematic review and meta-analysis - Zheng, Lei; Wang, Zuoping; Li, Yunxiang; Ge, Si; Zeng, Zhiqiang; Gan, Lijian; Meng, Chunyang; Li, Kangsen (Frontiers in Oncology, 2024)
ObjectiveThis review assessed the prognostic significance of the systemic immune inflammation index (SII) in patients with urothelial carcinoma.MethodsWe performed a systematic review and cumulative meta-analysis of the primary outcomes according to the PRISMA criteria, and assessed study quality. Seven databases were searched: Embase, PubMed, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, and SinoMed, from the creation of each database until October 2024.ResultsThe meta-analysis included 31 studies, including 14,437 patients with urothelial carcinoma. A low SII was significantly associated with better recurrence-free survival (RFS) (HR = 1.37, 95%CI (1.19, 1.56), P < 0.05), cancer-specific survival (CSS) (HR = 1.87, 95%CI (1.50, 2.34), P < 0.05), and overall survival (OS) (HR = 1.42, 95%CI (1.23, 1.64), P < 0.05). In addition, subgroup analysis found that higher SII was associated with poorer prognosis regardless of treatment regimen, tumor type, or SII cutoff, and that high SII was an important prognostic biomarker in the UC population.ConclusionA low SII may be associated with better RFS, CSS, and OS. The SII can be used as a is a potentially noninvasive and promising prognostic indicator for urothelial carcinoma; however, further studies with appropriate designs and larger sample sizes are needed to verify these findings.